Virtual Manipulatives: A Pathway to Enhancing Numeracy Skills in Inclusive Classrooms - Rahayu, Ni Komang Ari; Suarjana, I Made (International Journal of Elementary Education, 2024)
Mathematics instruction in inclusive classrooms often encounters challenges in delivering abstract material, such as basic multiplication facts, necessitating interactive and adaptive learning media. This study aims to analyze the design, validity, practicality, and effectiveness of instructional media based on virtual manipulatives. The study employed a one-group pretest-posttest design, collecting data through questionnaires and tests. Data analysis was conducted using qualitative, quantitative, and inferential statistical methods. The subject of this development is virtual manipulatives-based learning media, with the objects of practicality, validity, and effectiveness. The results revealed that the instructional media, developed using the ADDIE model, encompassed analysis, design, development, implementation, and evaluation stages. The media demonstrated excellent validity, with an average score of 3.90 from content experts and 3.88 from media experts. The media's practicality achieved a percentage of 95%, indicating its high feasibility. The effectiveness of the media was evaluated using a one-sample t-test, yielding a significance value of 0.000 < 0.05, indicating a significant improvement in students' numeracy skills after using the media The conclusion of this study shows that virtual manipulatives-based learning media innovation is effective and feasible to be used to improve students' numeracy skills in basic multiplication facts material in inclusive classes. These results contribute significantly to the development of innovative instructional media that address the needs of inclusive education.